Decision-making using fuzzy analytical hierarchy process in choosing postgraduate programs / Noraini Ahmad ...[et al.] - Ahmad, Noraini; Mohd Yusof, Zanariah; Jaffar, Ruhana; Shahrani, Nur Najihah (Unit Penerbitan UiTM Kelantan, 2018)
There are many postgraduate programs offered in public or private universities in Malaysia. Students can choose whether to further their study or not after completing their undergraduate study. If they choose to pursue their postgraduate studies, they can choose their study approach eithera coursework program or a research program. Most students who wish to pursue postgraduate studies have a problem in selecting the best program of study for them. By adopting the Fuzzy Analytical Hierarchy Process (FAHP) method, a decision-making instrument was constructed in this project to assist students to choose their postgraduate study program. In this research, seven main criteria were considered which were education, soft skills, time management, stress management, independence, teamwork and critical thinking. The weight of two main focuses which were research and coursework programs of each criteria was calculated using FAHP. The result indicates the students’ tendency to choose either research or coursework programs for their postgraduate study.